Combined Hysteroscopy and Laparoscopy in the Evaluation of Patients with Recurrent Pregnancy Loss - Khameneh, Maryam Khayyat (IIUM Medical Journal Malaysia, 2013)
Introduction: To determine the relative frequency of gynecological pathologies in patients with recurrent pregnancy loss using combined hysteroscopy and laparoscopy, and to evaluate the potential of this combined strategy in the diagnosis of coexisting pathologies. Methods: Over 6 years, in a large referral infertility clinic and research centre in Tehran, 80 women with the diagnosis of recurrent pregnancy loss underwent hysteroscopy and laparoscopy. Results: Forty nine (61.3%) women had 3 episodes of miscarriage, 9 (11.3%) had 4 occurrence of pregnancy loss and 14 (17.5%) patients had experienced 5 abortions. Also, there were 4 (5%), 2 (2.5%) and 2 (2.5%) participants with 6, 7 and 8 miscarriages, respectively. Thirteen women (16.2%) had normal hysteroscopy, and in 52 (65%) participant’s laparoscopy did not reveal abnormal findings. Septate uterus and submucous myomas together, comprised 62 (77.5%) of the recognized pathologies in hysteroscopy. Of the 28 abnormalities found in laparoscopy, 12 (43%) was endometriosis (15% overall) and the others were, pelvic and abdominal adhesions. Conclusion: Combined laparoscopy and hysteroscopy yields more satisfactory diagnostic results compared with hysteroscopy alone. Septate uterus, submucous myomas and endometriosis were common findings in patients with recurrent miscarriage. Especially, patients with recurrent pregnancy loss should be examined for the coexistence of endometriosis